Peran insektisida botani ekstrak biji mimba untuk konservasi musuh alami dalam pengelolaan serangga hama kapas. - Dwi Adi Sunarto; nurindah nurindah (Jurnal Entomologi Indonesia, 2009)
Natural Enemies Conservation: The Role of Neem-seed Extracts for Natural Enemies Conservation Used of Cotton Insect Pest Control. Insects associated with cotton plant are numerous, as the plant bears extrafloral nectar. More than 90 species of natural enemies are reported and identified. They could manage the cotton pest, keeping the pest population is under action threshold level when their presence is considered in scouting and action threshold concept. However, most of cotton farmers are insecticide-spray-minded people who think that insecticide sprays is a must in cotton cultivation. This behavior is unfavorable for the natural enemies in building their population so they can act as an effective mortality factor for the pest. Neem seed extract (NSE) is toxic to herbivores but relatively safe for natural enemies, so that it could be used as a substitute for synthetic chemical insecticides. Therefore, NSE is recommended to be used for conserving natural enemies in cotton agro ecosystem.